Vitamin K dietary intake is associated with cognitive function in an older adult Mediterranean population. (18th February 2022) - Camacho-Barcia, Lucía; García-Gavilán, Jesús; Martínez-González, Miguel Ángel; Fernández-Aranda, Fernando; Galié, Serena; Corella, Dolores; Cuenca-Royo, Aida; Romaguera, Dora; Vioque, Jesús; Alonso-Gómez, Ángel M; Wärnberg, Julia; Martínez, J Alfredo; et al.
Abstract: Background: In the last years, evidence that dietary vitamin K could have a role in the cognitive domain has increased. However, data from large trials are limited. The objective of this study was to assess the association of 2 year changes in the dietary intake of vitamin K with cognitive function measured through neuropsychological performance tests. Methods: In 5, 533 participants of the multicentre PREDIMED-Plus study (48.1% women, age 65.1 ± 4.9 years with overweight/obesity and metabolic syndrome), we assessed the adjusted odds ratios of cognitive function decline according to 2 year changes in vitamin K intake. Participants answered a battery of cognitive function tests and Food Frequency Questionnaires (FFQs) in order to estimate the vitamin K dietary intake. Results: After adjusting for potential cofounders, the highest tertile of change of dietary vitamin K intake (median [IQR]; 194.4 μg/d [120.9, 373.1]) was inversely associated with a Mini-Mental State Examination (MMSE) score ≤24 (OR [95% CI]; 0.53 [0.35, 0.79] P for trend = 0.002) compared with a decrease in the intake of vitamin K (median [IQR]; −97.8 μg/d [−292.8, −51.5]). A significant positive association between changes in dietary vitamin K intake and the semantic verbal fluency test scores (OR [95% CI]; 0.69 [0.51, 0.94] P for trend = 0.019) was found. Conclusions: An increase of the intake of dietary vitamin K was associated with better cognitive function scores, independently of recognised risk factors for cognitive decline, in an older adult Mediterranean population with high cardiovascular risk.